Studies on Storage Characteristics of Clarius batrachus at Different Temperatures - S.K., Battacharyya; D.R., Chaudhuri (Fishery Technology, 2025)
Storage characteristics of Clarius batrachus at three different temperatures, namely 37, 22 and 0Â°C (ice) are reported. Changes in moisture content, total volatile nitrogen, adenosine monophosphate, inosine monophosphate and total bacterial count during storage were studied. Organoleptically the fish had shelf-lives of 6h, 8.5h and 15 days at 37, 22 and oÂ°c respectively.